ASSESSMENT OF RISK FACTORS FOR THE DEVELOPMENT OF PELVIC-HEAD IMBALANCE. (Journal of Universal Science Research, 2024)
Childbirth is the final stage of pregnancy, and the condition of the mother and the newborn depends largely on the correct management, therefore, new high-tech research methods are developed for more effective management of pregnancy and childbirth [1]. Childbirth is a physiological process resulting in the birth of the baby and afterbirth. From the perspective of perinatal obstetrics, the main goal of childbirth is to ensure that the mother and newborn are healthy. In economically developed countries, childbirth is an almost safe process. Intrapartum mortality is less than 1% and maternal mortality is very rare. This has been achieved by taking into account the main factors that influence the course and outcome of childbirth. Uterine contractile dysfunction (UFD) remains an urgent and unresolved problem in modern obstetrics, and is the main cause of complications in labor and the postpartum period, both in women in labor and in newborns. According to different authors, the incidence of ARD varies from 9% to 33% [2].